Análise do consumo domiciliar de pescados no estado de São Paulo a partir da POF (2017-2018) utilizando técnicas de estatística multivariada e geoespacial - Santos, Nicolle Rye Fukushima dos [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Esta pesquisa teve como objetivo analisar os padrões de aquisição e consumo domiciliar de pescados no Brasil, com ênfase no estado de São Paulo, utilizando os microdados da Pesquisa de Orçamentos Familiares (POF 2017–2018) disponibilizados pelo IBGE. Apesar da ampla disponibilidade hídrica e do extenso litoral brasileiro, o consumo per capita de pescados permaneceu abaixo das recomendações da Organização das Nações Unidas para a Alimentação e Agricultura (FAO). Em regiões densamente povoadas como São Paulo, observou-se um consumo ainda mais reduzido, mesmo diante do avanço da produção aquícola nacional. A investigação considerou a influência de variáveis socioeconômicas, tais como idade, escolaridade, localização urbana ou rural, composição familiar e faixa de renda, sobre o padrão de consumo de diferentes tipos de pescados. As análises foram conduzidas no software R, por meio de estatística descritiva (médias, frequências e variâncias) e multivariada, incluindo alfa de Cronbach, análise de componentes principais, análise de correspondência, agrupamentos hierárquicos e bidimensionais. Adicionalmente, incorporaram-se técnicas de estatística geoespacial para explorar a dimensão territorial do consumo de pescados, permitindo mapear padrões espaciais de aquisição alimentar, identificar concentrações e disparidades regionais e relacionar esses resultados a características socioeconômicas e de infraestrutura municipal. Espera-se que os achados contribuam para a compreensão das desigualdades territoriais no acesso e na preferência por produtos da pesca e da aquicultura no estado de São Paulo.

This research aimed to analyze household acquisition and consumption patterns of fish in Brazil, with emphasis on the state of São Paulo, based on the microdata from the Consumer Expenditure Survey (POF 2017-2018) made available by the Brazilian Institute of Geography and Statistics (IBGE). Despite the country’s abundant water resources and extensive coastline, Brazil’s per capita fish consumption remains below the recommendations of the Food and Agriculture Organization of the United Nations (FAO). In densely populated regions such as São Paulo, this consumption is even lower, despite the national growth of aquaculture production. The study investigated the influence of socioeconomic variables - such as age, education, urban or rural location, presence of children and adolescents in the household, and income level - on the consumption patterns of different types of fish (freshwater, saltwater, prepared, fresh, frozen, among others). The analysis was conducted by constructing databases in the R software, using descriptive statistical techniques (means, frequencies, variances) and multivariate methods (Cronbach's alpha, principal component analysis, correspondence analysis, and hierarchical and bidimensional clustering). In addition, the research incorporated geospatial statistical techniques to explore the territorial dimension of fish consumption. This approach enabled the mapping of spatial patterns of food acquisition, the identification of regions with low or high consumption intensity, and the relationship of these results with the local socioeconomic and infrastructure context. The study aims to contribute to a broader understanding of territorial inequalities in access to and preference for fishery and aquaculture products.
Analysis of household fish consumption in the state of São Paulo based on the POF (2017–2018) using multivariate and geospatial statistical techniques
Keywords: Estatística; Consumo de pescados; Análise multivariada; Análise espacial; Pesquisa de orçamentos familiares; Statistic; Fish consumption; Multivariate analysis; Spatial analysis; Family budget survey